Strengthening the Religious Culture of Yasin and Tahlil through Mentoring Women’s Religious Gatherings in Kebonan Village, Clarak Hamlet, Klakah, Lumajang - Badria Badria; Nurhafid ishari; Faidur Robbani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Yasinan and tahlil activities are religious traditions that play an important role in strengthening religiosity, fostering social solidarity, and preserving Islamic values within community life. Previous studies have shown that the habituation of Yasin and tahlil recitations contributes to the enhancement of religious values, the development of Islamic character, and the reinforcement of religious culture in society. However, the sustainability of these activities often faces challenges, including limited understanding of their religious significance, suboptimal community participation, and the lack of continuous mentoring programs. This Community Service Program (PkM) aimed to strengthen religious culture through mentoring women’s religious gathering groups in conducting Yasinan and tahlil activities in Kebonan Village, Clarak Hamlet, Klakah District, Lumajang Regency. The target participants were women actively involved in routine religious activities within the community. The program employed a participatory approach through observation, coordination with community leaders, religious guidance, mentoring activities, and program evaluation. The intervention focused on assisting the implementation of Yasinan and tahlil activities, enhancing participants’ understanding of religious values, and encouraging greater participation and social interaction among members. The results indicated an increase in attendance and active participation, improved understanding of the religious meanings embedded in Yasinan and tahlil practices, and stronger social cohesion among community members. The program successfully contributed to the development of a sustainable religious culture and generated positive impacts on creating a more religious, harmonious, and participatory community environment.